2014
DOI: 10.1016/j.atherosclerosis.2013.11.029
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-133a regulates insulin-like growth factor-1 receptor expression and vascular smooth muscle cell proliferation in murine atherosclerosis

Abstract: Objective MicroRNA-133a (miR-133a) and insulin-like growth factor-1 (IGF-1) are two different molecules known to regulate cardiovascular cell proliferation. This study tested whether miR-133a affects expression of IGF-1 receptor (IGF-1R) and proliferation of IGF-1-stimulated vascular smooth muscle cells (VSMC) in a murine model of atherosclerosis. Methods and Results Expression of IGF-1R was analyzed by immuno-fluorescence and immuno-blotting, and miR-133a by qRT-PCR in the aortas of wild-type C57BL/6J (WT) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 31 publications
(43 reference statements)
0
47
0
2
Order By: Relevance
“…miRNAs pair with the messages of protein-coding genes to direct post-transcriptional repression [3] and target mRNAs based on sequence complementarity with target 3′-untranslated regions (3′-UTRs), leading to translational repression and/or to mRNA cleavage [4]. miRNAs are involved in cell differentiation [5], apoptosis [6], cell proliferation [7,8], division [9], protein secretion [10], immune regulation [11], viral infection [12], cancer development [13,14], invasion [15,16], tissue morphogenesis and growth [17,18], angiogenesis [19,20] and metastasis [21]. The largest functional group of miRNAs are those miRNAs involved in cancer development, and among these, some have been reported to function as oncogenic miRNAs or tumor suppressors, whereas others exert diverse functions [22].…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs pair with the messages of protein-coding genes to direct post-transcriptional repression [3] and target mRNAs based on sequence complementarity with target 3′-untranslated regions (3′-UTRs), leading to translational repression and/or to mRNA cleavage [4]. miRNAs are involved in cell differentiation [5], apoptosis [6], cell proliferation [7,8], division [9], protein secretion [10], immune regulation [11], viral infection [12], cancer development [13,14], invasion [15,16], tissue morphogenesis and growth [17,18], angiogenesis [19,20] and metastasis [21]. The largest functional group of miRNAs are those miRNAs involved in cancer development, and among these, some have been reported to function as oncogenic miRNAs or tumor suppressors, whereas others exert diverse functions [22].…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, miR-133 targeting Sp-1, which is needed for Klf4 activation to down-regulate myocardin, prevents myocardin repression of VSMC proliferation on PDGF-BB stimulation in vitro [17]. By contrast, Gao et al also reported that miR-133a enhances VSMC proliferation by stimulating IGF-1R expression, in a murine model of atherosclerosis [18].…”
Section: Discussionmentioning
confidence: 93%
“…However, miR-133 may play different roles in different types of cells. For example, it appears to have both positive and negative effects on proliferation, depending on the type of muscle cell, such as in C2C12 cells or balloon-injured vascular cells [17,18].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For example, it was recently reported that miR-133 inhibitor did not significantly affect rat VSMC proliferation, while miRNA-133 contributed to the cell phenotypical transformation and vascular muscle layer remodeling [27]. Furthermore, another study showed that miRNA-133a expression enhanced VSMC proliferation through promoting IGF-1R expression [28]. These findings reflect the complexity of the functions of miRNAs in regulating cell growth and proliferation.…”
Section: Discussionmentioning
confidence: 95%